Trends in ischaemic heart disease and cerebrovascular disease mortality in Europe: an observational study from 1990–2017. (25th November 2020) - Hammond-Haley, M; Hartley, A; Essa, M; Delago, A; Marshall, D.C; Salciccioli, J.D; Shalhoub, J.D
Abstract: Background: Cardiovascular disease remains the leading cause of death worldwide. Previously, we identified a growing disparity between Western and Eastern European countries for mortality from ischaemic heart disease (IHD) and cerebrovascular disease (CVD). Purpose: To describe current trends in mortality from IHD and CVD. Methods: IHD and CVD age-standardized death rates (ASDR) for European countries between 1990–2017 were extracted from the World Health Organization mortality database using the International Classification of Diseases 9th and 10th Edition codes. Jointpoint regression analysis was used to describe trends over this period. Results: Between 1990–2017, IHD mortality declined in all included countries except Croatia (+3% in males and +23% in females). Largest mortality improvements were generally seen in Western European countries, including the Netherlands, UK and Sweden, which saw greater than 65% improvements for both sexes. Estonia was a notable exception, which, after the Netherlands, demonstrated the second highest improvement in mortality (−69% in males, −74% in females). Hungary and Greece saw the smallest improvements in IHD mortality (approximately −12% to −27%). Results of jointpoint regression analysis for selected European countries are shown in Figure 1. In 2017 Lithuania had the highest mortality rate in both males and females (279.4/100, 000 and 261.3/100, 000, respectively) whilst the Netherlands had the lowest mortality in males and females (32.6/100, 00 and 15.3/100, 000, respectively). This represents an approximately 8.5-fold difference in IHD mortality in males and a 10.5-fold difference in females between these two countries. CVD mortality declined in all included countries between 1990–2017. Estonia saw the greatest improvements in both males and females (−80.8% and −84.9%, respectively), followed by Austria, Portugal and the Czech Republic (over 70% reductions in both sexes). Bulgaria, Romania and Lithuania saw the smallest reductions (approximately −17% to −33%). In 2017, Bulgaria had the highest CVD mortality rate in both males and females (149.9/100, 000 and 113.1/100, 000, respectively), whilst the lowest mortality rate was observed in Austria (21.8/100, 000 and 19.5/100, 000 for males and females, respectively). This represents an approximately 7-fold difference in CVD mortality in males and a 6-fold difference in females between these two countries. Conclusions: IHD and CVD mortality rates continue to decrease for men and women across Europe. While certain Eastern European countries have demonstrated considerable mortality improvements over this observation period, in general the disparity between Eastern and Western Europe persists, with further work required to understand and address these inequalities. Funding Acknowledgement: Type of funding source: None